Iowa Birdline update, March 28, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for March 28, 1994. Highlights include Sandhill Crane, Snowy Owl and Varied Thrush. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed